Influence of a Single Slow-Paced Breathing Session on Cardiac Vagal Activity in Athletes. - You, Min; Laborde, Sylvain; Salvotti, Caterina; Zammit, Nina; Mosley, Emma; Dosseville, Fabrice (International Journal of Mental Health & Addiction, 2022)
Introduction: Slow-paced breathing (SPB) is a well-known relaxation technique in athletes, which has also the potential to help optimize addiction treatments based on its effects on the autonomic nervous system. Specifically, these effects directly impact cardiac vagal activity (CVA), the activity of the vagus nerve regulating cardiac functioning. The effects of long-term SPB interventions on CVA have already received some attention; however, the effects of a single SPB session on CVA still require further investigation. Consequently, the aim of this study was to investigate the effects of SPB on CVA during, immediately after, and 60 min after a single SPB session. Methodology: Twenty-four athletes were involved in a within-subject design, with two conditions: slow-paced breathing (at 6 cycles per minute) and a control condition watching an emotionally neutral TV documentary while breathing at a spontaneous breathing rate. CVA was derived from heart rate variability measurement and indexed via the root mean square of successive differences, RMSSD. Results: Results showed that RMSSD measured during SPB was significantly higher than when measured before SPB, right after SPB, and 60 min after SPB. No changes were observed in the control condition. Discussion: Findings regarding concomitant effects of SPB on CVA are in line with previous literature. The return to baseline observed immediately after SPB and 60 min after SPB suggests that the effects on CVA are only transitory. Practical Implications: Given higher CVA has been linked to decreased cravings in addictions, future research should investigate to which extent SPB may be an effective technique to help coping with craving attacks on an acute basis.